Effect Analysis of Steel Sheet Pile Supporting for Utility Tunnel Foundation Pit in Water-Rich Soft Soil - Guotao Shao; Dan Tang; Duyun Tan; Zizhen Liu; Yongjian Zhu (Advances in Civil Engineering, 2023)
Given the structural stability of steel sheet pile support in a water-rich soft soil area, the interaction mechanical mechanism between steel sheet pile support and soft soil was analyzed in the paper. Based on the limit equilibrium theory of soil mass and the coordinated deformation effect of retaining structure and soil, the force equation and action coefficient considering the cohesion of soil and the friction angle of steel sheet pile to soil were obtained. According to the characteristics of the soil around the foundation pit, reasonable supporting spacing (d = 4 m) could be obtained considering the friction angle of the steel sheet pile to soil properly without the cohesion of soil. The monitoring results show that the axial force during the support process is more reasonable considering the cohesion of soil and the friction angle of interaction with the wall and soil. The axial force of the measuring point was affected by the construction site and the layout of the utility tunnel foundation pit. The location with large deformation of the steel sheet pile and the most unfavorable range from the top of the foundation pit was 0.5–0.7 H. For the mechanical analysis of the interaction between steel sheet pile and soil, the apparent cohesion and friction angle can be taken as 0.05 rH and φ/3–φ/2, respectively. The foundation pit in the water-rich soft soil area could operate stably with a better waterproof effect by the steel sheet pile under different working conditions.